Tata Motors' successful cross-border acquisition of Jaguar Land Rover: key take-aways. Issue 9 (12th September 2016) - Pathak, Atul Arun
Abstract : Purpose: This paper aims to focus on Tata Motors, an automobile company from an emerging market, and its successful acquisition of two global marquee car brands in Jaguar and Land Rover (JLR). It traces the evolution of JLR under the stewardship of Tata Motors over an eight-year long period and examines the strategic reasons for the success of the acquisition. Design/methodology/approach: The paper approaches strategic issues in cross-border acquisitions using an illustration of a successful deal. It is based on statements of leaders and secondary data about the acquirer and acquired organizations. The paper explores the strategic challenges faced when emerging market firms carry out cross border acquisition deals. It recommends the short-term and long-term strategies that acquirers can follow to improve the chances of a successful acquisition. Findings: Any acquisition is challenging. Cross-border acquisitions face greater challenges, especially if the acquirer is from an emerging market country while the target company is from a developed country. Success of the acquisition, especially over the long run, depends on both internal factors that are under the control of the acquirer's management, as well as external environmental factors that it needs to address. Both patience and luck are required ingredients for success in such contexts. Practical implications: While the general temptation in any acquisition is to extract synergies as quickly as possible, the Tata Motors' acquisition of JLR is an exception. Tata Motors carefully handled short-term challenges and continued to invest in the core competencies of JLR and reaped benefits over the long run. It was also fortunate that a variety of factors in the external environment turned favorable for Tata Motors and JLR in the eight years since the deal took place. Social implications: It concedes that during an M&A deal, the leaders of a seller organization may be nervous about their future. JLR trade union leaders were initially not sure whether jobs in UK would remain secure. To ensure success of the deal, the leaders of the acquirer firm need to balance the interests of multiple stakeholders, both in the short-term, as well as over a longer-term perspective. Originality/value: The paper considers the Tata Motors' acquisition of JLR. It is an example of a large, difficult cross-border acquisition by an emerging market based company. While the acquisition proved difficult in the short term, it has yielded excellent dividends to the parent company over the long term. This paper explores the reasons why this cross-border acquisition succeeded and recommends strategies that other companies considering cross-border acquisitions can consider to improve their chances of success.